STRATEGI PENGEMBANGAN DESA WISATA DI KELURAHAN JELEKONG, KABUPATEN BANDUNG - Sumantri, Diaz (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2018)
Tourism is one of the priorities of the national development in the fields of economy, tourism development including forms of village tourism. Based on the decision letter of the Regent of Bandung Number 556.42/Headers. 71-Dispopar/2011, Jelekong Village is one that is established as a village, because the votes have characteristic patterns of social life of the community in the form of a unique culture puppetry and painting and puppet craftsman. To develop the area into a tourist village, required an appropriate strategy based on the potential of the resource. The approach that the author use descriptive research, namely through the survey method with variable single research namely development potential of the tourist village, where aspects of the physical aspect i.e. the charge indicators will be, social, spatial, buildings, culture, crafts and ceremonies, as well as supporting other tourism indicators such as accessibility, accommodation, community, tourists and tourism managers. As for the results of the study showed that the potential Wards Jelekong village embodiment based on criteria, classified into class II i.e. enough potential to be developed. Attitude and positive values indicate community participation in supporting its development. Based on the results of the SWOT analysis, the strategies that can be used in Jelekong village development that is developing and organizing potential attractions; preservation of customs; accessibility improvements; develop various infrastructure supporting tourism; partnering with related stakeholders and investors; improving promotion; engaging the public in every stage of the development of village tourism.